Epidemiology of gout in the United Kingdom and Taiwan - Kuo, Chang-Fu (2014)
Background: Gout is the most common inflammatory arthritis worldwide. The hallmarks of initial gout presentation are acute pain, swelling, erythema and tenderness in peripheral joints but eventually unremitting arthritis, joint deformity and tophus deposition may develop with long-standing hyperuricaemia. Patients with gout suffer not only arthritis but also cardiovascular, renal, metabolic and other comorbidities. Since gout is the consequence of chronic hyperuricaemia, urate-lowering treatments (ULT) helps prevent the formation of urate crystals and promote dissolution of existing crystals.